Antennal Electrophysiological Responses of Three Parasitic Wasps to Caterpillar-Induced Volatiles from Maize (Zea mays mays), Cotton (Gossypium herbaceum), and Cowpea (Vigna unguiculata) - Gouinguené, Sandrine; Pickett, John A.; Wadhams, Lester J.; Birkett, Michael A.; Turlings, Ted (My University, 2005)
Many parasitic wasps are attracted to volatiles that are released by plants when attacked by potential hosts. The attractiveness of these semiochemicals from damaged plants has been demonstrated in many tritrophic systems, but the physiological mechanisms underlying the insect responses are poorly understood. We recorded the antennal perception by three parasitoids (Cotesia marginiventris, Microplitis rufiventris, and Campoletis sonorensis) to volatiles emitted by maize, cowpea, and cotton plants after attack by the common caterpillar pest Spodoptera littoralis. Gas chromatography-electroantennography (GC-EAG) recordings showed that wasps responded to many, but not all, of the compounds present at the physiologically relevant levels tested. Interestingly, some minor compounds, still unidentified, elicited strong responses from the wasps. These results indicate that wasps are able to detect many odorant compounds released by the plants. It remains to be determined how this information is processed and leads to the specific behavior of the parasitoids.
Keywords: GC-EAG - electrophysiology - Cotesia marginiventris - Microplitis rufiventris - Campoletis sonorensis - induced plant odor